Deslocamentos urbanos e desigualdades sociais: um estudo do movimento diário da população de Belo Horizonte - Arnaldo Lopo Mont Alvao Neto (2009)
This dissertation consists in a sociological analysis of people daily dislocations, which are taken as an important variable to analyze the social organization of an urban space. The dissertation focuses on the relationship between daily dislocations, transportation system and social inequalities, expressed by different patterns of time and space uses. The main data set used for the study is a Time Use Research, articulated with information collected from another study, the Origin and Destination Research. The results suggest that social inequalities and transportation modes are important dimensions to the understanding of dislocation patterns and the general access to the city. This way, those dimensions must be considered for public policies regarding to the transportation system.